Mitral valve replacement in infants and younger children - Ahmed F. Elmahrouk (Nature Portfolio, 2021)
Abstract Data on mitral valve replacement (MVR) in young children is still limited. Our objective was to evaluate MVR in children below 5 years and identify factors affecting the outcomes. This retrospective study included 29 patients who had MVR from 2002 to 2020. We grouped the patients into two groups according to their age: age ≤ 24 months (n = 18) and > 24 months (n = 11). Primary cardiac diagnoses were Shone complex (n = 7; 24%), isolated congenital mitral valve abnormality (n = 11; 38%), and complete atrioventricular septal defect (n = 3; 10%). The median age was 19 month (25th–75th percentile: 11–32) and 59% were females (n = 17). The hemodynamic lesions were mitral regurgitation in 66%, mitral stenosis in 10%, and combined mitral stenosis and regurgitation in 24% of the patients. St. Jude mitral valve was the most common valve implanted (n = 19, 66%), followed by CarboMedics in 21% of the patients (n = 6). The mitral valve was implanted in the supra-annular position in 6 cases (21%). Preoperative and operative data were comparable between both groups. There was no association between valve size and position with postoperative heart block (P > 0.99, for both). The median follow-up duration was 19.4 months (8.6–102.5). Nine patients had mitral valve reoperation, six had MVR, and three had clot removal from the mitral valve. There was no effect for age group on reoperation (SHR 0.89 (95% CI 0.27–2.87), P = 0.84). Valve size significantly affected reoperation (SHR 0.39 (95% CI 0.18–0.87), P = 0.02). The supra-annular position was associated with an increased risk of reoperation (SHR 3.1 (95% CI 1.003–9.4), P = 0.049). There was no difference in survival according to the age (Log-rank P = 0.57) or valve size (Log-rank P = 0.66). Mitral valve replacement in children is associated with low morbidity and mortality. The risk of reoperation could be affected by the valve size and position rather than the age.